Investigation of Physicochemical Properties of PVA-GANT Mucoadhesive Hydrogels - Nazneen Malek; Irina Ermonlina; Vitaliy V Khutoryanskiy; Ellen V Hackl (University of Huddersfield Press, 2018)
The aim of this work was the manufacture and characterisation of novel chemically cross-linked mucoadhesive PVA-GANT hydrogels prepared by using autoclaving. Particularly, the study was focused on the physicochemical and pharmaceutical properties of these hydrogels with regards to potential applications for drug delivery and wound dressing. PVA-GANT hydrogels with different molar ratios and total concentrations of polymers in solution were prepared using a standard sterilisation autoclave. The physico-chemical properties were characterised by various techniques including IR spectroscopy, Texture Analysis and SEM and thermo-analytical techniques (DSC and TGA). Pharmaceutical characteristics were obtained in drug loading/release tests and microbiological assays. The results have shown that the properties of hydrogels (swelling degree, mechanical properties, internal structure, drug loading/release and antimicrobial properties) are very dependent on the polymer composition.